Risk factors for Human Immunodeficiency Virus in South-South Nigeria - Ochei, Uche. M.; Ozolua, Raymond I. (The Nigerian Journal of Pharmacy, 2013)
Background: HIV/AIDS is a global pandemic that has continued to pose a maiorthreatto public health especially in the resource poor regions of the world. The purpose of the study wasto investigate how some factors impact on HIV infection in the south-south geopoliticalzone ofNigeria. Method: The study was carried out using government hospitals in the six states in the zone comprising Edo, Delta, Bayelsa, Rivers, Akwa-ibom and Cross River. The study design was a cross sectional survey and the population were HIV positive and Hlv negative subjects who accessed drugs in the Pharmacy department of the selected hospitals. The main study instrument was a structured questionnaire and purposive sampling was used. A total of 1250 questionnaires were distributed based on subject traffic in each of the hospitals and the distribution was as follows: Edo-450, Delta-300, Bayelsa- 100, Rivers-150, Akwa Ibom-130, Cross River-120. The usable questionnaires returned was 955 (76.4%) and in this order Eclo-415 (92.2%), Delta-249 (83.0%), Bayelsa-69 (69.0%), Rivers-101 (67.3%), Akwa~ lbom 68(S2.3%} and Cross Rivers-3 (44.2%). Data collected from the questionnaires was analyzed using a graph-Pad Prism Software (UK), Chi- square and simple percentages. Results: Out of the 955 respondents 33.7% were males while 66.3% were females and also 61.3% of the respondents were HIV positive while 38.7% were HIV negative. From the results, respondents who had sexually transmitted infections (STls) had a high rate of contracting HIV. increase in the number of sexual partners increases infection while condom use significantly reduced the chances of infection (Condom users, 26.2%, non- users 73.8%). Blood transfusion was an effective mode of transmission of the virus and accounted for 37.1% of the cases. Conclusion: Multiple sex partners, non-use of ' condoms, blood transfusion and ST_Is especially gonorrhea were factors associated with increased risk of contracting HIV infection in the South-South geopolitical zone of Nigeria. Educational interventions targeting these factors needsto be stepped up.